DISCUSSION ON CHARACTERISATION IN SOUTH AFRICAN PRIVATE INTERNATIONAL LAW (The Pretoria Student Law Review, 2021)
To inform those unfamiliar to the subject, private international law is simply that branch of a country’s domestic law, which regulates the relationship between private individuals when foreign legal rules are in some way concerned. This branch generally has three subbranches: Jurisdiction (choice of court), choice of law and recognition of foreign judgments. The discipline of characterisation forms part of the choice of law sub-branch and is explained further below. This article discusses the problem of a ‘gap’ arising from the phenomenon of characterisation in South African private international law, by considering the current case law authorities on the matter as well as the criticisms (and suggested solutions) of legal academics. A general discussion of characterisation, with some alternative suggestions for dealing with the problem, is also mooted for consideration in a bid to air ideas. No short work could do justice to the problem visited here. This work seeks to show that the obsession with characterisation in the choice of law arena is perhaps ill founded and should perhaps be simplified in favour of a ‘most natural results’ approach.
Keywords: private international law; characterisation; choice of law; South African private international law